Investigating the factors related to severity of nausea and vomiting during Pregnancy and how it is controlled by pregnant Women in Hamadan, 2014 - Soodabeh Aghababaei; Ali Reza Soltanian; Shokoufeh Sharifi; Elnaz Torkzaban; Mansoureh Refaei (Mashhad University of Medical Sciences, 2019)
Introduction: Nausea and vomiting can reduce the quality of life of pregnant women. Identifying the related factors and how we can relieve them can play an important role in the care of pregnant women. Therefore, the present study was conducted with aim to determine the factors affecting the severity of nausea and vomiting during pregnancy and how it is controlled by mothers. Methods: This descriptive study was performed on 160 pregnant women with gestational age of 6-20 weeks and single pregnancy who had referred to Hamadan health centers in 2014. Data were collected by using the researcher-made questionnaire including the questions about demographic characteristics, fertility, how to control nausea and vomiting, and the questionnaire of assessing nausea and vomiting in pregnancy. Data were analyzed by SPSS software (version 16) and Fisher Exact test. P < 0.05 was considered significant. Results: According to the results of the study, the severity of nausea and vomiting was mild in 79 cases (49.4%), moderate in 75(46.9%) and severe in 6 (3.7%). Maternal age, mother's occupation, gestational age and time of day were associated with severity of nausea and vomiting (P<0.05). 89 (56.2%) of the research units were looking for a remedy for their problem by using of herbal compounds and medicine. Vitamin B6 and mint extract were most used. 80 (50%) of women did not use any medicines due to their fear of injury to the fetus. Conclusion: Variables such as maternal age, mother's occupation, gestational age and time of occurrence of nausea and vomiting during the day were related to the severity of nausea and vomiting. Vitamin B6 and Mint extract had the most intake for relieving nausea and vomiting during pregnancy.